2016
DOI: 10.3390/ijms17081203
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Characterization of Carboxypeptidase Genes in Silkworm (Bombyx mori)

Abstract: The silkworm (Bombyx mori) is an economically-important insect that can secrete silk. Carboxypeptidases have been found in various metazoan species and play important roles in physiological and biochemical reactions. Here, we analyzed the silkworm genome database and characterized 48 carboxypeptidases, including 34 metal carboxypeptidases (BmMCP1–BmMCP34) and 14 serine carboxypeptidases (BmSCP1–BmSCP14), to better understand their diverse functions. Compared to other insects, our results indicated that carboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
1
3
0
2
Order By: Relevance
“…Previous studies have shown that carboxypeptidases found in the midgut are involved in the release of free amino acids from food proteins. The study also demonstrated that midgut-specific carboxypeptidases were downregulated after starvation and restored after the refeeding of the larvae . There is a massive increase in feed intake in the fifth instar of the silkworm larvae as they prepare to spin silk and metamorphose into other stages, and as such, the upregulation of MSTRG.5590 in this study is not surprising.…”
Section: Results and Discussionsupporting
confidence: 67%
“…Previous studies have shown that carboxypeptidases found in the midgut are involved in the release of free amino acids from food proteins. The study also demonstrated that midgut-specific carboxypeptidases were downregulated after starvation and restored after the refeeding of the larvae . There is a massive increase in feed intake in the fifth instar of the silkworm larvae as they prepare to spin silk and metamorphose into other stages, and as such, the upregulation of MSTRG.5590 in this study is not surprising.…”
Section: Results and Discussionsupporting
confidence: 67%
“…The exopeptidases are further divided into carboxypeptidases (cleaving at the carboxylic terminus) and aminopeptidases (cleaving at the amino terminus). A total of 48 genes encoding carboxypeptidases have been identified in silkworm and midgut-specific carboxypeptidases were significantly downregulated after starvation and restored after re-feeding [49]. A total of 9 carboxypeptidases were successfully identified in silkworm digestive juice; among them, BGIBMGA004830, BGIBMGA009486, and BGIBMGA004797 were upregulated in DJ48/24h.…”
Section: Discussionmentioning
confidence: 99%
“…Carboxypeptidase B-like can be tracked to the gene BmMCP18 that encodes a metallocarboxypeptidase with Peptidase_M14 domain and a divalent metal (zinc) cation in its active site (206). In mammals, carboxypeptidase B can modulate the coagulation cascade in the plasma (207) but in insects it remains unknown whether a protease cascade is involved in the clotting process (208).…”
Section: Cluster 16 ("Oenocytoid")mentioning
confidence: 99%